2013
DOI: 10.1111/asj.12061
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification procedure decreases inositol 1,4,5‐trisphophate receptor expression, resulting in low fertility of pig oocytes

Abstract: Although cryopreservation of mammalian oocytes is an important technology, it is well known that unfertilized oocytes, especially in pigs, are highly sensitive to low temperature and that cryopreserved oocytes show low fertility and developmental ability. The aim of the present study was to clarify why porcine in vitro matured (IVM) oocytes at the metaphase II (MII) stage showed low fertility and developmental ability after vitrification. In vitro matured cumulus oocyte complexes (COCs) were vitrified with Cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Accordingly, an increased frequency of non-penetrated parthenogenetic oocytes was observed in the matured-vitrified group in the present study. A plausible explanation for this phenomenon may be alteration or damage of Ca 2+ regulating organelles such as mitochondria and the endoplasmic reticulum, as reported previously in mouse, porcine and human oocytes [8][9][10]15].…”
Section: Discussionmentioning
confidence: 77%
“…Accordingly, an increased frequency of non-penetrated parthenogenetic oocytes was observed in the matured-vitrified group in the present study. A plausible explanation for this phenomenon may be alteration or damage of Ca 2+ regulating organelles such as mitochondria and the endoplasmic reticulum, as reported previously in mouse, porcine and human oocytes [8][9][10]15].…”
Section: Discussionmentioning
confidence: 77%
“…Vitrification and warming by the Cryotop method was performed as describe [28] with some modification. PN embryos were selected and exposed for 10 min to PB1, i.e., phosphate-buffered saline (PBS) supplemented with 20% (v/v) fetal calf serum (FCS), 15% (v/v) ethylene glycol (EG) and COOH-PLL.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining was carried out as previously described (Hirose et al . ). Following three washes in phosphate‐buffered saline (PBS) (Nissui, Tokyo, Japan) containing 0.1% polyvinyl alcohol (PBS‐PVA), oocytes were fixed for 60 min in PBS‐PVA containing freshly prepared 2% (w/v) paraformaldehyde and 0.2% (v/v) Triton X at 24°C.…”
Section: Methodsmentioning
confidence: 97%
“…Our previous study confirmed that the CT1 antibody can be used for detection of IP 3 R1 in pig oocytes (Hirose et al . ). Following primary antibody incubation, oocytes were washed with PBS‐BSA (three times for 15 min each) and incubated for 1 h in a secondary antibody (Alexa 488 anti‐rabbit immunoglobulin G (IgG)) diluted 1:100 in PBS‐BSA at 24°C.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation